Feasibility of high-intensity resistance training sessions in cancer survivors - Schlüter, Kathrin; Schneider, Justine; Rosenberger, Friederike; Wiskemann, Joachim (Journal of strength and conditioning research, 2022)
Schlüter, K, Schneider, J, Rosenberger, F, and Wiskemann, J. Feasibility of high-intensity resistance training sessions in cancer survivors. J Strength Cond Res 36(9): 2643-2652, 2022—Moderate-intensity resistance training (MIRT) is regarded as safe in cancer survivors (CS), but for high-intensity resistance training (HIRT), evidence is lacking. Hence, in the current exploratory analyses, single sessions of HIRT are compared with MIRT regarding safety and feasibility. Twenty-three of 24 included CS (14 breast and 10 prostate CS, 61.6 ± 9.5 years, body mass index 27.0 ± 4.3 kg·m−2, 6-52 weeks after end of primary therapy) started a 12-week resistance training (RT) with a daily undulating periodization model including HIRT (90% of 1 repetition maximum [1RM]) and MIRT (67% 1RM) sessions. Parameters of safety (adverse events [AEs] and training-related pain), feasibility (physical and mental exhaustion, sensation of effort, enjoyment, and dropout rate), and adherence were assessed. An alpha level of 0.05 was applied for analyses. Nineteen of 23 training starters (83%) completed all sessions. Fourteen minor AEs occurred. A significantly higher increase for physical exhaustion appeared in HIRT (p < 0.001). For 18% (HIRT) and 19% (MIRT) of the sessions, training-related pain was reported with no significant difference between intensities. In total, 34% of HIRT and 35% of MIRT sessions were perceived as overstraining or partly overstraining with no significant difference between intensities, but enjoyment (median and quartiles on a 1-7 scale) was high for both (HIRT = 5 [5;6] and MIRT = 5 [4,6]). Our analysis indicates that HIRT sessions do not differ from MIRT sessions concerning safety or feasibility, but training-related pain should be monitored. RT protocols incorporating high-intensity training loads can be applied safely in breast and prostate CS.
Gesehen am 14.09.2022